Civil activity of Vasyl Prohoda during the emigration in ČSSR (1922–1939) - Kravets, Natalia (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
In the article, the fields of civil activity of Vasyl Prohoda, a Ukrainian military figure (Lieutenant Colonel of the Army of the Ukrainian National Republic), a public figure, engineer, and a historian are analyzed in Czechoslovakia. His civil activity in the development of the Ukrainian Economic Academy (“Academic community”) and the “Society of former soldiers of the Army of the UNR”, the Ukrainian Sokol movement is described. The failures of the Ukrainians in the national liberation actions of 1917–1921 led to the forced relocation of many participants abroad. Among the leading centers of the Ukrainian interwar emigration, the Czechoslovak Republic (ČSSR) was distinguished by its liberal political regime and democratic freedoms. Due to the fortunate conditions, Ukrainian emigrants formulate various networking of public-political organizations, created to protect the interests of Ukrainian emigrants in the international environment, and to continue their professional activities abroad. They launched also cultural-educational and scientific activities. The study clarifies the ideological priorities of Vasyl Prohoda, his active organizational, educational and ideological components of civil activity in the above-mentioned organizations. The purpose of this article is to analyze the civil activity of Vasyl Prohoda in the Ukrainian emigration in the ČSSR in the interwar period of the twentieth century. The goal involves solving the following tasks: 1) find out the fields of civil activities during studying in the Ukrainian Economic Academy (UEA); 2) conducted civil activity in 1920–1930s. In particular, the study presents the activities of Vasyl Prohoda in the Academic Community of UEA, "The Community of Former Army of the UNR", the Agrarian Community, the Ukrainian Sokol movement.

Artykuł analizuje kierunki aktywności społecznej Wasyla Prochody, ukraińskiego działacza wojskowego i społecznego okresu międzywojennego w Czechosłowacji. Scharakteryzowano czynny udział w rozwoju Ukraińskiej Akademii Gospodarczej, Towarzystwa Byłych Żołnierzy Armii UNR oraz Ukraińskiego Ruchu Sokolskiego. Po I wojnie światowej, ukraińskiej rewolucji dziesiątki tysięcy najbardziej aktywnych obywateli Ukrainy, głównie żołnierzy armii ukraińskiej, wyjechało na emigrację. Większość z nich przebywała w Czechosłowacji, gdzie mieli możliwość zdobycia wykształcenie na uczelniach ukraińskich i czechosłowackich. Wasyl Prochoda, jeden z przywódców ukraińskiego ruchu emigracyjnego w międzywojennej Czechosłowacji, był ukraińskim działaczem wojskowym, społecznym i politykiem, podpułkownikiem armii UNR, historykiem. Brał czynny udział w działalności Ukraińskiej Akademii Gospodarczej w Podiebradach, działalności kulturalnej i edukacyjnej, tworzył różne stowarzyszenia, organizacje, grupy. Celem artykułu jest analiza aktywności społecznej Wasyla Prochody w środowisku emigracji ukraińskiej w Czechosłowacji w dwudziestoleciu międzywojennym. Aby go osiągnąć podjęto refleksję dotyczącą W ramach tej refleksji podjęto następujące problemy badawcze 1) analiza kierunków aktywności społecznej podczas studiów w Ukraińskiej Akademii Gospodarczej; 2) analiza działalności społecznej pod koniec lat dwudziestych – w latach trzydziestych XX wieku.
Keywords: Vasyl Prohoda; civil activity; the Ukrainian Sokol movement; Wasyl Prochoda; aktywność społeczna; Ukraiński Ruch Sokolski